Quantitative assessment of parameters that affect strength development in alkali activated fly ash binders. (15th September 2015) - Kazemian, Ali; Gholizadeh Vayghan, Asghar; Rajabipour, Farshad
Highlights: Activator composition can be described using only two essential parameters: modulus ( n ) and alkalinity (pH). Concurrent increase in n and pH is desirable for achieving high strength binders. There is an optimum liquid to solid ratio to achieve highest compressive strength. Extended steam curing can profoundly impact strength development of binders. Statistical study proves the significance of the selected combination of parameters in estimating the compressive strength. Abstract: The influence of activator composition (pH, modulus), activator to fly ash ratio, (L/S)vol, and curing on strength development of alkali activated fly ash (AAFA) mortars is investigated. A statistical analysis is performed to evaluate the significance of these parameters and to develop a preliminary regression model for predicting the 1-day strength. The results show that to achieve high strengths, activators with very high pH (⩾15.0) or high pH and moderate modulus (pH ⩾ 14.75, n  ⩾ 0.75) are needed. Such activators have high viscosity and lead to low workability. AAFA strength does not monotonically increase with reducing (L/S)vol, but is maximum at intermediate (L/S)vol .